Visual and Technological Transformation Analysis in the Adaptation of the Digital Comic “Lookism” Into Animation - Renzy Ayu Rohamatilah; Nila Rahmawati; Abdul Rahman Prasetyo (EDUTEC : Journal of Education And Technology, 2025)
The development of digital technology make changes in the process of adapting visual artworks to other media, especially from webtoons to animation. Animated adaptations not only emphasize similarities to the original work, but also about representing the story experience using digital technology, including motion graphics, sound effects, as well as animation techniques. This research aims to analyze visual transformation and technological innovation in the process of adapting webtoons to animation. This study uses a descriptive qualitative approach through observation and literature study. The results of the study show that digital technology acts as a mediator that expands the experience of presenting stories through increasing the rhythm of the story and the emotional involvement of the audience. However, the use of technology also poses challenges related to the equalization of animation with the originality of the work and the adjustment of visual elements to the animation medium. The transfer of rides from webtoons to animation is a creative process that makes the medium of work more diverse